Efeitos do fraturamento hidráulico em aqüiferos fissurais - Santos, José Sérgio dos (2008)
The demand of the people for more water has forced the development of techniques to improve the use of all forms of water resources. In some parts of the United States of America, hydraulic fracturing has been used to stimulate wells drilled in crystalline basement to increase its flow. In northeastern Brazil, the wells drilled in this type of geological formation often exhibit low flow, which leads to subsequent deactivation or simple neglect. The main objective of this research is to study, analyze and quantify the effects of hydraulic fracturing prints on transmissivity, connectivity and flow of a fissure aquifer. Therefore we developed a model of propagation of fractures in shallow formations and waterproof matrix. In addition, use was made of well hydraulics models for the determination of the hydrodynamic parameters of the aquifer. To test the methodology, data collected at two pumping wells drilled in the Horticultural Farm of University of New Hampshire, Durham, NH, were used. This data includes pre-fracturing pumping tests and post-fracturing, geophysical testing in addition to the fracturing operation records. A joint analysis of the results of pumping tests and fracture propagation model concluded that hydraulic fracturing increased transmissivity of fractures in 46 times in one well and 285 times in another. The connectivity of the fracture system experienced increases between 11 and 20 times. The practical data was a well spent to provide flow rates 10 times higher and the other this increase was 18 times. These improvements were possible because hydraulic fracturing extended the opening of fractures and made her beam spread for tens of meters. The distance that the fracture propagated from the well along with the increase in interconnection fractures connected the well to recharge the most favorable regions.